A Role for Lipid Rafts in B Cell Antigen Receptor Signaling and Antigen Targeting - Cheng, Paul C. (The Rockefeller University Press, 1999)
The B cell antigen receptor (BCR) serves both to initiate signal transduction cascades and to target antigen for processing and presentation by MHC class II molecules. How these two BCR functions are coordinated is not known. Recently, sphingolipid- and cholesterol-rich plasma membrane lipid microdomains, termed lipid rafts, have been identified and proposed to function as platforms for both receptor signaling and membrane trafficking. Here we show that upon cross-linking, the BCR rapidly translocates into ganglioside GM1-enriched lipid rafts that contain the Src family kinase Lyn and exclude the phosphatase CD45R. Both Igα and Lyn in the lipid rafts become phosphorylated, and subsequently the BCR and a portion of GM1 are targeted to the class II peptide loading compartment. Entry into lipid rafts, however, is not sufficient for targeting to the antigen processing compartments, as a mutant surface Ig containing a deletion of the cytoplasmic domain is constitutively present in rafts but when cross-linked does not internalize to the antigen processing compartment. Taken together, these results provide evidence for a role for lipid rafts in the initial steps of BCR signaling and antigen targeting.